Prostate‐specific antigen modulates the osteogenic differentiation of MSCs via the cadherin 11‐Akt axis. Issue 1 (15th May 2020) - Wu, Longxiang; Xiang, Shiqi; Hu, Xiheng; Mo, Miao; Zhao, Cheng; Cai, Yi; Tong, Shiyu; Jiang, Huichuan; Chen, Linxiao; Wang, Zhi; Xiong, Wei; Ou, Zhenyu
Abstract: Background: A high prevalence of osteoblastic bone metastases is characteristic of prostate cancer. Prostate‐specific antigen (PSA) is a serine protease uniquely produced by prostate cancer cells and is an important serological marker for prostate cancer. However, whether PSA modulates the osteogenic process remains largely unknown. In this study, we explored the effect of PSA on modulating the osteoblastic differentiation of mesenchymal stem cells (MSCs). In this study, we used flow cytometry, CCK‐8 assay, Alizarin red S (ARS) staining and quantification, alkaline phosphatase (ALP) activity and staining, Western blotting, and quantitative real‐time PCR (qRT‐PCR) to explore the effect of PSA on osteogenic differentiation of MSCs. Results: We first demonstrated that although PSA did not affect the proliferation, morphology, or phenotype of MSCs, it significantly promoted the osteogenic differentiation of MSCs in a concentration‐dependent manner. Furthermore, we demonstrated that PSA promoted the osteogenic differentiation of MSCs by elevating the expression of Cadherin 11 in MSCs and, thus, activating the Akt signaling pathway. Conclusions: In conclusion, we demonstrated that PSA could promote the osteogenesis of MSCs through Akt signaling pathway activation by elevating the expression of cadherin‐11 in MSCs. These findings imply a possible role of PSA in osteoblastic bone metastases in prostate cancer.